Improving Ocimum basilicum productivity in newly reclaimed soils using poultry manure and salicylic acid - Yousef Mahmoud; Elsayed Hammad; Atef Abdel-kader (Mesopotamia Journal of Agriculture)
This study investigated the impacts of poultry manure (PM) as an organic manure and salicylic acid (SA) as a plant growth stimulant on sweet basil growth and essential oil over two growing seasons (2023 and 2024). Poultry manure was applied to the soil at rates of 0.0, 4.0, 8.0, and 12.0 m³/fed, while salicylic acid was applied as a foliar spray [0 (control), 50, 100, 150, and 200 ppm]. The results demonstrated that both poultry manure (PM) application at all levels and foliar spraying with salicylic acid (SA) at all concentrations significantly increased plant height, number of branches per plant, dry weights of both herb and leaves, essential oil content, and N, P, and K percentages in the leaves dry across all three harvests in both seasons. The highest PM level (12 m³/fed) consistently resulted in the highest growth values. Furthermore, the 150 ppm SA treatment was the most effective foliar application for enhancing the studied traits across all cuts. Significant interaction effects were observed for all examined parameters. The treatment with the greatest PM level (12 m³/fed) and 150 ppm SA was shown to be the most beneficial for all cuts.